Vitamin K epoxide reductase complex subunit 1 (VKORC1) gene polymorphism as determinant of differences in Covid-19-related disease severity. (November 2020) - Janssen, Rob; Walk, Jona
Abstract: Covid-19, caused by SARS-CoV-2, has major world-wide health-related and socio-economic consequences. There are large disparities in the burden of Covid-19 with an apparent lower risk of poor outcomes in East Asians compared to populations in the West. A recent study suggested that Covid-19 leads to a severe extrahepatic vitamin K insufficiency, which could lead to impaired activation of extrahepatic proteins like endothelial anticoagulant protein S in the presence of normal hepatic procoagulant activity. This would be compatible with the enhanced thrombogenicity in severe Covid-19. The same study showed that vitamin K antagonists (VKA) that inhibit vitamin K recycling, had a greater impact on procoagulant activity than on the activation of extrahepatic vitamin K-dependent proteins during SARS-CoV-2 infections. A genetic polymorphism in the vitamin K epoxide reductase complex 1, VKORC1 −1639A, is particularly prevalent in East Asia and associates with low vitamin K recycling rates. Carriage of the allele may be regarded as bioequivalent to low-dose VKA use. We speculate that VKORC1 −1639A confers protection against thrombotic complications of Covid-19 and that differences in its allele frequency are partially responsible for the differences in Covid-19 severity between East and West.